2019
DOI: 10.1182/blood-2018-08-868752
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax combined with decitabine or azacitidine in treatment-naive, elderly patients with acute myeloid leukemia

Abstract: Older patients with acute myeloid leukemia (AML) respond poorly to standard induction therapy. B-cell lymphoma 2 (BCL-2) overexpression is implicated in survival of AML cells and treatment resistance. We report safety and efficacy of venetoclax with decitabine or azacitidine from a large, multicenter, phase 1b dose-escalation and expansion study. Patients (N = 145) were at least 65 years old with treatment-naive AML and were ineligible for intensive chemotherapy. During dose escalation, oral venetoclax was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
1,416
5
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,430 publications
(1,476 citation statements)
references
References 38 publications
43
1,416
5
12
Order By: Relevance
“…It is noteworthy that BCL2 inhibitors, such as venetoclax (ABT‐199), are clinically explored in several cancer types . However, studies have indicated that the expression levels of anti‐apoptotic proteins, BCL2, Bcl‐xL, and Mcl‐1, are highly variable, manifesting various disease prognosis and venetoclax sensitivity . Thus, further studies are needed to explore whether BCL2 upstream genes, such as HOXA10, could help develop new therapy strategies for GC.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that BCL2 inhibitors, such as venetoclax (ABT‐199), are clinically explored in several cancer types . However, studies have indicated that the expression levels of anti‐apoptotic proteins, BCL2, Bcl‐xL, and Mcl‐1, are highly variable, manifesting various disease prognosis and venetoclax sensitivity . Thus, further studies are needed to explore whether BCL2 upstream genes, such as HOXA10, could help develop new therapy strategies for GC.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, median OS from venetoclax initiation was significantly longer in patients with primary HMA refractory disease compared to HMA‐responders (126 days vs 15 days; P = 0.018). In previous AML studies, patients with a WBC exceeding 25 G/L were excluded from venetoclax treatment . Despite a baseline WBC of up to 269 G/L (range 0.7‐269 G/L) at venetoclax initiation, we did not observe tumor lysis syndrome.…”
Section: Resultsmentioning
confidence: 68%
“…In clinical studies, although the selective BCL‐2 inhibitor venetoclax has modest activity as monotherapy in R/R AML, more impressive results have been observed in two phase 1b/2 studies using venetoclax in combination with either HMA or LDAC in older (≥65 years) patients with newly diagnosed AML unfit for intensive chemotherapy. In a study of 145 patients, venetoclax plus azacitidine or decitabine produced a CR/CRi in 67%, median OS lasting 17.5 months and 46% were alive at 2 years . Similarly, in study of 82 patients (prior HMA exposure allowed), venetoclax plus LDAC (20 mg/m 2 subcutaneous daily d1‐10) produced a CR/CRi in 54%, median OS lasting 10.1 months and 44% were alive at 1 year .…”
Section: Challenging the Notion That Treating Older Patients With Amlmentioning
confidence: 97%